The effectiveness of face-to-face versus online delivery of continuing professional development for science teachers: a systematic review - Li, Zhi; Che Hassan, Norlizah; Ab. Jalil, Habibah (Multidisciplinary Digital Publishing Institute, 2023)
Purpose: This systematic review assesses the effectiveness of face-to-face and online delivery modes of continuing professional development (CPD) for science teachers. It focuses on three aspects: evaluating the effectiveness of these modes, summarizing the literature on the factors influencing them, and conducting a comparative analysis of their advantages. Methods: The research team employed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) method and the Mixed Methods Appraisal Tool (MMAT) for article quality assessment. A total of 12 articles, selected from a potential 82, were included in the study. Results: This research suggests that the face-to-face and online CPD modes are equally effective and that external factors, such as psychological variables and establishing communication communities, influence their effectiveness. Face-to-face CPD fosters communication communities, while online CPD offers geographical flexibility and cost-saving benefits. Implications: The effectiveness of face-to-face and online CPD relies on external psychosocial factors. Future research should focus on strategies to enhance participants’ communication engagement in online communities. Additionally, it is worth conducting further investigations of the potential relationships between psychosocial variables and the effectiveness of online CPD, along with the impact of digital skills on online CPD.